The Right to Privacy: Constitutional Perspective in India - Dr. Sunil Khosla (Innovative Research Thoughts, 2017)
A prominent and ever-changing element of constitutional law around the globe is the right to privacy, which is frequently portrayed as a protector of personal freedom and autonomy. The right to privacy has become an extremely important concept in India, a country that is well-known for its cultural diversity and diverse array of rights and freedoms. This paper examines the historical-legal basis, and current obstacles to the right to privacy in the Indian Constitution, illuminating how has it changed the social and legal environment. A democratic and rights-based society is laid forth in the Indian Constitution. Although not specifically stated, the right to privacy is enshrined in the Constitution's basic rights, especially Articles 19 and 21. The right to privacy is a fundamental human right, and this study follows its evolution through time by looking at the verdicts of the Court that helped establish this principle.